2023
DOI: 10.1002/trc2.12371
|View full text |Cite
|
Sign up to set email alerts
|

Functional connectivity and mild behavioral impairment in dementia‐free elderly

Abstract: Background Mild behavioral impairment (MBI) is a syndrome that uses later‐life emergent and persistent neuropsychiatric symptoms (NPS) to identify a group at high risk for incident dementia. MBI is associated with neurodegenerative disease markers in advance of syndromic dementia. Functional connectivity (FC) correlates of MBI are understudied and could provide further insights into mechanisms early in the disease course. We used resting‐state functional magnetic resonance imaging (rs‐fMRI) to tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 57 publications
(120 reference statements)
1
21
1
Order By: Relevance
“…In this regard, finding that one symptom of a neurodegenerative disease predicts another would be unsurprising but to definitively show this requires imaging and biomarker studies that can determine etiology. [33][34][35][36][37][38] Our findings provide a clear rationale for such studies.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…In this regard, finding that one symptom of a neurodegenerative disease predicts another would be unsurprising but to definitively show this requires imaging and biomarker studies that can determine etiology. [33][34][35][36][37][38] Our findings provide a clear rationale for such studies.…”
Section: Discussionmentioning
confidence: 65%
“…However, implied within our hypotheses is that, for some, both MBI‐psychosis and the cognitive endpoint of IQCODE >3.6 are sequelae of a common underlying neurodegenerative disease. In this regard, finding that one symptom of a neurodegenerative disease predicts another would be unsurprising but to definitively show this requires imaging and biomarker studies that can determine etiology 33–38 . Our findings provide a clear rationale for such studies.…”
Section: Discussionmentioning
confidence: 79%
“…Previous research has indicated that reduced functional connectivity between the PCC and ACC is linked to declines in memory function and overall cognitive ability [53]. This finding has been confirmed by fMRI studies focusing on mild behavioral impairment, mild cognitive impairment, and early stages of Alzheimer's disease, among other disorders [2,40,54]. As such, ACC functional connectivity can serve as a neuroimaging biomarker for cognitive decline.…”
Section: Discussionmentioning
confidence: 69%
“…This evidence gap warrants further investigation. We investigated the relationship between menopausal symptoms and later-life changes in cognitive function and behaviour; both risk factors for dementia, which may also represent preclinical/prodromal AD 14,15,42,43,[48][49][50][51][52][53][54][55] . We hypothesized that individuals who experienced a greater number of menopausal symptoms (i.e., greater menopausal symptom burden) would subsequently experience poorer cognitive function and greater MBI symptom burden compared to individuals who experienced fewer menopausal symptoms.…”
Section: Introductionmentioning
confidence: 99%